2020
DOI: 10.1002/jcb.29708
|View full text |Cite
|
Sign up to set email alerts
|

FAM20C phosphorylation of the RGDSVVYGLR motif in osteopontin inhibits interaction with the αvβ3 integrin

Abstract: Osteopontin (OPN) is a ubiquitously expressed, multifunctional, and highly phosphorylated protein. OPN contains two neighboring integrin-binding motifs, RGD and SVVYGLR, which mediate interaction with cells. Phosphorylation and proteolytic processing affect the integrin-binding activities of OPN. Here we report that the kinase, FAM20C, phosphorylates Ser 146 in the 143 RGDSVVYGLR 152 motif of OPN and that Ser 146 is phosphorylated in vivo in human and bovine milk. Ser 146 is located right next to the RGD motif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“… 21 Moreover, Schytte et al recently reported that the phosphorylation of an OPN construct, which covers the integrin binding motif, and full-length OPN, co-expressed with Fam20C, strongly hampers the interaction with α v β 3 integrin. 66 OPN is not only the most phosphorylated substrate of Fam20C but also a natural binder to integrin receptors. 48 Thus, its phosphorylation may have a major impact on the mediation of cell–ECM adhesion properties through integrin binding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 Moreover, Schytte et al recently reported that the phosphorylation of an OPN construct, which covers the integrin binding motif, and full-length OPN, co-expressed with Fam20C, strongly hampers the interaction with α v β 3 integrin. 66 OPN is not only the most phosphorylated substrate of Fam20C but also a natural binder to integrin receptors. 48 Thus, its phosphorylation may have a major impact on the mediation of cell–ECM adhesion properties through integrin binding.…”
Section: Resultsmentioning
confidence: 99%
“…Thereby, it abolishes energetically favorable interactions between OPN sites that are distant from the canonical RGD motif and integrin receptors. 48 , 66 However, the central part that contains the (integrin binding) RGD motif (residues 159–161) retains its local rigidity ( 15 N R 2 rates) and maintains a preformed template for receptor recognition.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we determined how could SPP1, a secreted protein, function through PKCα. Previous studies have reported that SPP1 interacted with many cell types via various receptors, including CD44 and integrins (αvβ3, αvβ1, αvβ5, αvβ6, α8β1, α5β1, α9β1, and α4β7) [14,34]. However, receptors have been reported to be expressed on SCs including CD44, αvβ3, αvβ8, α1β1, α2β1, α6β1 and α7β1 [31,32].…”
Section: Cd44 and αVβ3 Were Upregulated In Scs After Sciatic Nerve Inmentioning
confidence: 98%
“…CD44 and αvβ3 were upregulated in SCs after sciatic nerve injury in rats Next, we determined how could SPP1, a secreted protein, function through PKCα. Previous studies have reported that SPP1 interacted with many cell types via various receptors, including CD44 and integrins (αvβ3, αvβ1, αvβ5, αvβ6, α8β1, α5β1, α9β1, and α4β7) [14,34]. However, receptors have been reported to be expressed on SCs including CD44, αvβ3, αvβ8, α1β1, α2β1, α6β1 and α7β1 [31,32].…”
Section: Spp1 Promoted Sc Proliferation and Inhibited Apoptosis Throumentioning
confidence: 98%